INFLUENCE OF CAPITAL STRUCTURE, COMPANY GROWTH, COMPANY SIZE AND PROFITABILITY ON COMPANY VALUE IN INSURANCE COMPANIES (Jurnal Ipteks Terapan, 2022)
This observation was conducted in order to determine the effect of capital structure, firm growth, firm size and profitability on firm value. The results of the t-test in this study show that only profitability has a significant effect on firm value. The results of the f test on this observation indicate that the capital structure, firm growth, firm size and profitability do not simultaneously affect firm value